THE FARRAR-GLAUBAR APPROACH IN TESTING FOR MULTICOLLINEARITY IN ECONOMIC DATA - Joseph, Akinniyi Alaba; Ademoh, Sanni Eneji (International Journal For Research In Business, Management And Accounting, 2018)
This research aims at determining the presence of Multicollinearity in a function using farrar-glaubar test approach. In most economic data, there is the presence of Multicollinearity but the severity varies. The degree of this multicollinearity may vary from function to function. However, Farrar-Glaubar test is used to detect the presence and severity of Multicollinearity, location of Multicollinearity, and the pattern of Multicollinearity in a function. How to correct the effect of Multicollinearity was also covered this research. After analyses were done on the collected data, we realized that, Multicollinearity is most pronounced in Economic data.